(a) lim x -3^+ x+2x+3
(b) lim x -3^- x+2x+3
© lim x 1 2-x(x-1)^2
(d) lim t 5^- e^t(t-5)^3
(e) lim x 3^+ ln (x^2-9)
(f) lim x 2^- x^2-2 xx^2-4 x+4
(g) lim x 2^+ x^2-2 x+8x^2-5 x+6

Exercícios relacionados

(a) lim x 4 raiz5 x^2-2 x+3
(b) lim x -1 x-2x^2+4 x-3
© lim x 8(1+raiz[3]x)(2-6 x^2+x^3)
(d) lim t -1(t^2+1)^3(t+3)^5
(e) lim x 1(1+3 x1+4 x^2+3 x^4)^3
(f) lim u -2 raizu^4+3 u+6
(g) lim x 2 x^2+x-6x-2
(h) lim x -4 x^2+5 x+4x^2+3 x-4
(i) lim x 2 x^2-5 x+6x-2
(j) lim x 4 x^2-4 xx^2-3 x-4
(k) lim h 0 (4+h)^2-16h
(l) lim x 1 x^3-1x^2-1
(m) lim x -2 x+2x^3+8
(n) lim t -3 t^2-92 t^2+7 t+3
(o) lim h 0 (2+h)^3-8h
(a) y = (2 x + 1) / (x - 2)
(b) y = (x^2 + 1) / (2 x^2 - 3 x - 2)
© y = (2*x^2 + x - 1) / (x^2 + x - 2)
(d) y = (1 + x^4) / (x^2 - x^4)
(e) y = (x^3 - x) / (x^2 - 6x + 5)
(f) y = 2 e^x / (e^x - 5)
y = (x^2 + 1) / (3x - 2x^2)
(a) f(x) = (2x + 3) / (x - 2), (2, infinito).
(b) g(x) = 2 * raiz(3 - x), (-infinito, 3].